(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the oral health condition of children and adolescents, verifying the prevalence of dental caries according to sex and age in students from elementary school in João Pessoa-PB, using the CPO-D and CEO-d indexes. It was an epidemiological, descriptive research, based on bibliographical study and can be characterized as observational of a transversal nature, through the intensive direct technique, with a quantitative approach. Of the 412 students, the sample totaled 52 children between 5 and 12 years old, being 31 female (59,6%) and 21 male (40,4%). The instrument for data collection was an evaluation form with the date of the examination, age and gender of the participants, as well as a model for filling out the dental chart. The collected data were stored in the StatisticalPackage for Social Sciences (SPSS) for Windows, version 20.0 database and analyzed using descriptive statistics. According to the results, it is observed that the evaluated students have a low prevalence of tooth decay both in primary dentition with a mean CEO-D value of 0.84, and in permanent dentition with a mean CPO-D of 1.04, satisfactory in relation to the national average. The importance of implementing and continuing education, prevention and oral health promotion programs aimed at this population was concluded, and the need for greater dental care, especially in primary dentition, was highlighted.